2009
DOI: 10.1038/mp.2009.90
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impact of genetic variation of the serotonin transporter in primates is associated with differences in brain morphology rather than serotonin neurotransmission

Abstract: A powerful convergence of genetics, neuroimaging and epidemiological research has identified biological pathways mediating individual differences in complex behavioral processes and related risk for disease. Orthologous genetic variation in non-human primates represents a unique opportunity to characterize the detailed molecular and cellular mechanisms which bias behaviorally- and clinically-relevant brain function. We report that a rhesus macaque orthologue of a common polymorphism of the serotonin transporte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(132 citation statements)
references
References 57 publications
(99 reference statements)
11
120
1
Order By: Relevance
“…When incongruent, it modulates the activity of downstream brain areas that are involved in response selection and action, such as the amygdala and striatum. In that way, increased OFC activity may allow short-allele carriers to flexibly adapt behaviour when a mismatch is detected between the expected and actual outcome of behaviour, for instance during reversal learning in rhesus macaques (Jedema et al 2009). …”
Section: Neural Mechanisms Of Epigenetic Programmingmentioning
confidence: 98%
See 1 more Smart Citation
“…When incongruent, it modulates the activity of downstream brain areas that are involved in response selection and action, such as the amygdala and striatum. In that way, increased OFC activity may allow short-allele carriers to flexibly adapt behaviour when a mismatch is detected between the expected and actual outcome of behaviour, for instance during reversal learning in rhesus macaques (Jedema et al 2009). …”
Section: Neural Mechanisms Of Epigenetic Programmingmentioning
confidence: 98%
“…The cognitive enhancement is also consistent with the observation that short-allele carriers show increased processing of negative feedback (Althaus et al 2009). In rhesus monkeys, the short-allele of the rh5-HTTLPR was associated with superior performance on an array of cognitive tasks: the probability discounting task, the delay discounting task, the reversal learning task and the delayed match-to-sample task (Jedema et al 2009). The better performance in the probability discounting task is consistent with the increased attention to high and low probabilities in the risky decision-making task in humans carrying the short 5-HTTLPR variant (Roiser et al 2006) and may be explained by augmented cortico-limbic activation (Fallgatter et al 1999(Fallgatter et al , 2004 and superior ability to integrate feedback information over time to guide behaviour on subsequent choices (Althaus et al 2009).…”
Section: Neural Mechanisms Of Epigenetic Programmingmentioning
confidence: 99%
“…Genetic studies have tied this neuromodulatory pathway to social behavior in humans and other primates, with variants of two serotonergic genes having been examined in particular depth: a variable insertion in the gene encoding tryptophan hydroxylase (TPH2), the rate limiting enzyme in serotonin synthesis, and the 5HTTLPR (serotonin-transporter-linked polymorphic region) polymorphism within the promoter region of the serotonin transporter gene (SLC6A4, solute carrier family 6 member 4). Both variants have orthologs in humans and rhesus macaques, have been associated with altered development of several brain regions (135,136), and may influence the intensity and duration of signaling at serotonergic synapses (135,137).…”
Section: Genetic Regulation Of Social Behaviormentioning
confidence: 99%
“…2 In addition, rhesus macaque models have also shown that brain morphology varies more by SERT variation than does in vivo SERT or serotonin concentration. 3 Thus, SERT gene alleles have been reported to be involved in phenotypes, endophenotypes and anatomical structure. Serotonin balance at the synaptic cleft is modulated by the serotonin transporter encoded by the serotonin transporter gene commonly known as HTT, SLC6A4 or SERT (herein referred to as SERT).…”
Section: Introductionmentioning
confidence: 99%